2017
DOI: 10.5487/tr.2017.33.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Toxic Heavy Metal, Co(II) Trace via Voltammetry with Semiconductor Microelectrodes

Abstract: The cobalt (Co(II)) ion is a main component of alloys and considered to be carcinogenic, especially due to the carcinogenic and toxicological effects in the aquatic environment. The toxic trace of the Co(II) detection was conducted using the infrared photodiode electrode (IPDE) using a working electrode, via the cyclic and square-wave anodic stripping voltammetry. The results indicated a sensitive oxidation peak current of Co(II) on the IPDE. Under the optimal conditions, the common-type glassy carbon, the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Research has revealed that there is an increased chance of cancer after exposure to genotoxic metals, such as chromium VI, cobalt, and nickel, in cosmetic products. [68][69][70][71][72][73] In other studies, heavy metals, such as lead, cadmium, and chromium, in pigments of lipstick, eye shadow, lip makeup, and face powder may lead to cancerous and noncancerous effects on human health. 70,74 Use of commercially available moisturizing creams increases the chances of tumor formation when applied topically to UVB-pretreated high-risk mice.…”
Section: Cosmetics and Cancermentioning
confidence: 99%
“…Research has revealed that there is an increased chance of cancer after exposure to genotoxic metals, such as chromium VI, cobalt, and nickel, in cosmetic products. [68][69][70][71][72][73] In other studies, heavy metals, such as lead, cadmium, and chromium, in pigments of lipstick, eye shadow, lip makeup, and face powder may lead to cancerous and noncancerous effects on human health. 70,74 Use of commercially available moisturizing creams increases the chances of tumor formation when applied topically to UVB-pretreated high-risk mice.…”
Section: Cosmetics and Cancermentioning
confidence: 99%